Assembly and development of large active calderas hosting geothermal systems: Insights from Los Humeros volcanic complex (Mexico). (December 2022) - Carrasco-Núñez, G.; Cavazos-Álvarez, J.; Dávila-Harris, P.; Bonini, M.; Giordano, G.; Corbo-Camargo, F.; Hernández, J.; López, P.; Lucci, F.
Abstract: Caldera volcanoes are complex geological systems that show, during and after their formation, a wide variability in terms of eruptive styles, magmatic and geochemical evolution, and volcanic structures. Los Humeros Volcanic Complex (LHVC) is a key area where to study these factors. It is located in the easternmost sector of the Trans-Mexican Volcanic Belt and hosts an active geothermal system. LHVC exemplifies the complex nature of calderas, recording periods of alternated effusive and explosive eruptive phases, a heterogenous magmatic source, diverse basaltic to rhyolitic products, and the overlapping of caldera collapse events. This study provides an up-to-date interpretation of the caldera framework. Our work is based on a detailed analysis of literature and novel data aimed at the morpho-structural caldera configuration, and supported by geophysical modeling, and petrology of the volcanic products. The new results confirm a more complex evolution of LHVC involving geometric configurations related to multiple caldera collapse events producing both asymmetric trapdoor, and piecemeal styles. The present configuration of the caldera framework involved the initial formation (at 164 ka) of a large caldera (Los Humeros) of ca. 15–17 km diam (shorter than previously reported), which was overlapped asymmetrically by the younger (69 ka) and smaller (ca. 8.5–10 km diam) Los Potreros caldera over the west side, as a result of multiple sequential collapsing events. The final configuration of the caldera rims (scarps) was promoted by incremental growth. A post-caldera resurgence phase was induced by the injection of multiple shallow intrusions of silicic bodies, causing a more localized deformation of the caldera floor. The Holocene volcanism records the recurrent injection of compositionally distinct magma batches uprising from different depths of the LHVC transcrustal magmatic plumbing system. This latter indicates the transition from the caldera stage magmatic system dominated by a single, large, and shallow magmatic body to a more complex, polybaric post-caldera stage plumbing system, made up of a lower crust mafic reservoir feeding smaller magma batches vertically distributed in the whole crust. The integration of all the existing data constitutes the archive to better understand how large active calderas hosting exploitable geothermal systems assemble through time. Highlights: Assembly of caldera structures is key to understand the origin and evolution of caldera complexes. A more accurate caldera rim configuration for both Los Humeros and Los Potreros calderas is unraveled. Los Potreros caldera was formed by at least two caldera-forming events supported by field, DEMs and MT evidence. Caldera rim configuration resulted from the overlapping of Los Potreros over Los Humeros caldera, causing a damage zone. LHVC magma reservoir evolved from a single large chamber to a vertically-distributed plumbing system.